JAWARA DALAM PERUBAHAN SOSIAL DI MASYARAKAT BANTEN - Ato’ullah Ato’ullah (Jurnal Ilmiah Mimbar Demokrasi, 2014)
Jawara is part of the social structure in society since time immemorial Banten which consists of, ulama, umaro, and jawara. Because of its advantages supernatural, they actually have a noble obligation which protect the society and defend the interests of religion. However, after the transfer of power from the sultanate to the colonial government, the social structure of ulama-umaro-jawara change become, jawara-umaro-ulama. Their position in society became stronger and shifted their political behavior for the purposes of economic interests. In this context , they are trying to maintain the legitimacy of the leadership provided by the local culture. They tried to control the strategic institutions in economics and local politics while stabilizing external network to establish a good relationship with other elite, such as bureaucrats, party and military. This relationship is symbiotic, which stresses the advantages for each party. With a system of government that adopts oligarchy and conditions such Banten, the development of democracy and civil society in Banten became a very serious issue.